Differentiating Gender and Sex in Dental Research: A Narrative Review. (23rd August 2022) - Alberti, Alice; Morandi, Benedetta; Francetti, Luca; Taschieri, Silvio; Corbella, Stefano
Abstract : While in humans the term "sex" refers to the biological attributes that distinguish subjects as male, female, and intersex, the term "gender" refers to psychological, social, and cultural factors that strongly influence attitudes, behaviors, and relationships of individuals. Recently, it has been emphasized how the integration of these two terms in the design of the research can improve the methodology of the research itself. However, in dental research, the influence of gender has not gained enough consideration and it is often used indiscriminately as a synonym for sex. This narrative review discusses the usefulness of considering gender and sex in dental research, whose guidelines have been provided so far on this topic, and whether the top 20 dental scientific journals promote the analysis of sex and gender in their guidelines. Sex and gender analysis in dental research could be important both for analyzing biological differences such as those in the immune or neuro-immune system, cardiovascular physiology, developmental anomalies or deformities, and psychosocial differences such as lifestyle, pain experience and prevalence of chronic pain, eating behavior, and access to healthcare services. As for the specific policies for sex and gender analysis and reporting, only five out of 20 biomedical journals have included them in their editorial policy, which refers mainly to the correct use of the terms "sex" and "gender." In conclusion, we found that no specific and differentiated sex and gender analysis and reporting are required in dental journals. Their integration, which is still not routinely applied, may be improved in the future by updating editorial guidelines and developing more specific methodological recommendations.